The contribution of the directors to the development of Federal Agricultural Research Center of the North-East named N. V. Rudnitsky (to the 130th anniversary of the organization) - I. A. Ustyuzhanin; V. A. Starikov (Аграрная наука Евро-Северо-Востока, 2025)
The article provides the results of research and production work of the team of scientists of Federal Agricultural Research Center of the North-East named N. V. Rudnitsky, starting from 1895, the date of establishment the Vyatka Zemsky Agricultural Experimental Station. There has been revealed the role of 18 directors in the establishment and development of the organization in different conditions of our country existence.